Day-ahead Clearing Method for High-proportion Hydropower Electricity Market - ZHANG Yang; SHEN Jianjian; ZHAO Qihao; XIE Mengfei; JIA Zebin (Renmin Zhujiang)
How to handle the complex characteristics of cascade hydropower and solve the competitive spillage and power shortage problem is one of the key issues in the clearing of the high-proportion hydropower day-ahead spot electricity market.Therefore,combined with the project in Yunnan,this paper proposes a day-ahead clearing method for the high-proportion hydropower electricity market.In this method,the hydraulic constraints in the clearing model are replaced by the post-hydraulic check.Combined with the essential causes of competitive spillage and power shortage problems,the paper constructs a conditional constraint set including cascaded hydropower linkage constraints and spillage control constraints,and corresponding trigger conditions respectively.Moreover,the constraint boundaries are dynamically updated to gradually reduce competitive spillage and power shortage in the iterative solution procedure.A settlement compensation strategy is finally designed to provide corresponding benefits for plants involved in solving the spillage.The proposed method is validated by a real-world hydropower-dominated provincial system ranking second in China.The results show that competitive spillage and power shortage can be avoided or reduced substantially.It is demonstrated that this method meets the requirements of practicability and timeliness for day-ahead spot clearing of hydropower-dominated provincial power systems.